THE POSSIBILITIES OF ENDOSCOPIC ULTRASONOGRAPHY IN THE DIAGNOSTICS OF SOLID PANCREATIC NEOPLASMS - N. S. Ryabin; A. N. Katrich; M. I. Bykov; R. G. Stash (Кубанский научный медицинский вестник, 2018)
Endosonography takes a leading role in solid pancreatic neoplasms diagnostics. This article presents the main indicators of diagnostics efficiency of the method depending on the nosology of a tumor. The article describes the research results of domestic and foreign authors about the possibility of endoscopic ultrasonography in determining the resectability of solid pancreatic neoplasms based on the diagnostics of biliopancreatoduodenal zone blood vessels invasion. We consider the auxiliary techniques of endosonography, particularly, their role and informative value in differential diagnosis of pancreatic lesions.